Konsumsi Pangan dan Pemanfaatan Pekarangan Pada Masa Pandemi Covid–19 di Kecamatan Kasihan, Kabupaten Bantul, DIY - Agus Nugroho Setiawan; Muhammad Agustian; Sarjiyah Sarjiyah (Jurnal Penelitian Pertanian Terapan, 2023)
One of the areas affected by the Covid-19 pandemic is Kasihan District, Bantul, DIY. Covid-19 in Kasihan has not only impacted the health sector but has also caused massive economic disruption. This research aims to determine food consumption patterns and utilization of yards during the Covid-19 pandemic. This research was conducted from March to April 2022 with an observation location in Kasihan Bantul, using survey techniques, distributing questionnaires, and interviewing the community. Data were obtained from 152 respondents from 4 sub-districts and 53 hamlets, which were then analyzed descriptively. The results showed that the food consumption pattern of the people in Kapanewon Kasihan Bantul during the Covid-19 pandemic experienced slight changes, with a decrease in the level of food fulfillment by 1.32% and an increase in the frequency of consuming fruit and vegetables. The yard in Kapanewon Kasihan Bantul has been used by the community for plant cultivation, livestock, and fish farming for a long time and has not changed during the Covid-19 pandemic. The yard in Kapanewon Kasihan Bantul has not been effective in meeting food needs and increasing family income during the Covid-19 pandemic.